The Role and Significance of Hagiography as Agent of Healing in the Ethiopian Orthodox Täwahédo Church: the Case of Dérsanä Rufaýel (e-Journal of Linguistics, 2025)
This article examines the connection between Dérsanä Rufaýel and the healing methods evident in EOTC tradition and liturgy. The purpose of the study is to demonstrate Dérsanä Rufaýel's impact on the healing of illnesses and other related issues. The author's content analysis from the majority of his doctoral dissertation serves as the study's primary source. In addition to Dérsanä Rufaýel, intertextual analysis has also received attention, encompassing other important texts such as the Book of Enoch and the Déggwa of Saint Yared. In certain regions of Ethiopia, the study also involves the indirect monitoring of healing services conducted in certain St. Raphael's churches. According to the research, one of the easily accessible liturgical books on the theme of healing in the EOTC is Raphael's Homily. It is also mentioned in Mäséhäfä Sénksar throughout the yearly and monthly festivities. Therefore, healing is primarily associated with devotion to the magnificent archangel Rufaýel. The EOTC's devout pilgrims commemorate the days of the archangel and use the holy water to cure themselves of illnesses and other issues. Insofar as it opens up new avenues for study across the humanities, the relationship between ancient literature and modern considerations is fascinating.
Keywords: Archangel; Dérsanä Rufaýel; Homily; Holy Water; Ethiopian Orthodx Täwahédo Church (EOTC)